EXPLORING SUSTAINABILITY FACETS OF PRO-POOR TOURISM PROGRAMS IN INDIA - Vinodan, A; Sethumadhavan, Meera; Manalel, Jamaes (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
This paper intends to explore local-specific sustainability facets of pro-poor tourism initiated in India’s Protected Area (PA). Mixed methodology, i.e., interview and structured questionnaire adopted for data collection and followed by the factor analysis for testing hypothesis. The result indicates that the sustainability facets of pro-poor tourism have five distinct facets: monetary, environmental, societal, cultural heritage, and governance. The study assumes significance in the pro-poor approach in tourism development for addressing various Sustainable Development Goals and in understating the ground-level reality of sustainability in the context of tourism-led development in developing countries. It also throws light on setting standards for approach-based tourism programs that cater to various segments of society and the environment.